Science teachers’ teaching actions in their classrooms: Pedagogical content knowledge and skills - Imran Tufail, Chris Eames, Maurice M.W.Cheng (JSE, 2023)
Abstract This study offers empirical evidence of science teachers’ teaching actions in their classrooms comprising a combination of knowledge components and teaching skills (PCK&S). Pedagogical Content Knowledge (PCK) is a combination of knowledge components for teaching (Mavhunga, 2020;